Orally Dispersible Dosage Forms for Paediatric Use: Current Knowledge and Development of Nanostructure-Based Formulations - Andreea Cornilă; Sonia Iurian; Ioan Tomuță; Alina Porfire (MDPI AG, 2022)
The paediatric population has always suffered from a lack of medicines tailored to their needs, especially in terms of accurate dosage, stability and acceptability. Orodispersible dosage forms have gone through a resurrection as an alternative to liquid formulations or fractioned solid formulations, although they are still subject to several inconveniences, among which the unpleasant taste and the low oral bioavailability of the API are the most significant hurdles in the way of achieving an optimal drug product. Nanostructures can address these inconveniences through their size and variety, owing to the plethora of materials that can be used in their manufacturing. Through the formation and functionalisation of nanostructures, followed by their inclusion in orodispersible dosage forms, safe, stable and acceptable medicines intended for paediatric use can be developed.